PELATIHAN DAN PENDAMPINGAN PENDAFTARAN MEREK DAGANG BAGI PELAKU USAHA MIKRO KECIL MENENGAH (KUB SEJAHTERA) DI PEKANBARU - Nizar, Rini; Khairani, Zulia; Ihsan, Fikratul (Diklat Review : Jurnal manajemen pendidikan dan pelatihan, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in Indonesia's national economy. Despite contributing significantly to GDP and employment, MSMEs face challenges in protecting their intellectual property rights (IPR), particularly in registering trademarks. This community engagement activity aimed to enhance the understanding and capabilities of MSMEs in the Sejahtera Business Group (KUB) in Pekanbaru regarding trademark registration and packaging design as essential elements of branding and product competitiveness. The method employed was Participatory Rural Appraisal (PRA), emphasizing active participation from the identification of challenges to the implementation of solutions. The training involved theoretical sessions, interactive discussions, and practical demonstrations focusing on trademark registration procedures, intellectual property rights protection, and the role of packaging in strengthening market appeal. Post-training, participants were provided with intensive mentoring to address technical barriers in trademark registration. Evaluation results revealed significant improvements in participants’ knowledge and confidence in registering trademarks and designing effective packaging. More than 95% of participants reported satisfaction with the program, highlighting its practicality and relevance to their business needs. The findings suggest that comprehensive and sustained interventions in branding and IPR protection can enhance the competitiveness and sustainability of MSMEs. This program serves as a model for empowering small businesses through education and mentorship in intellectual property management